EFEKTIVITAS PENDAMPINGAN BERBASIS SEKOLAH LAPANG DALAM PENGEMBANGAN TANAMAN PADI DI DESA BONGOHULAWA KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - sulastri djafar; Asda Rauf; Ramlan Mustafa (Universitas Wahid Hasyim, 2025)
Rice crop development is a series of efforts and strategies undertaken to increase the productivity, quality, and sustainability of rice production. This study aims to determine the internal and external factors affecting the effectiveness of field school-based mentoring in rice crop development and analyze the effectiveness of field school-based mentoring in rice crop development in Bongohulawa Village, Tilongkabila District, Bone Bolango Regency. A total of 50 rice farmers participated in the field school. The analysis used in this study was descriptive analysis and effectiveness analysis. The results showed that internal factors such as age, education level, length of farming, land area, and land ownership status influenced the effectiveness of field school-based mentoring. Meanwhile, external factors such as the role of extension workers and the availability of information also contributed significantly to the effectiveness of field school-based mentoring by 81.2%. The implementation of field school-based mentoring in Bongohulawa Village has been quite effective. This is reinforced by the results of the analysis of each indicator consisting of knowledge, attitudes, and skills having an effectiveness value of 74.24%.